PERGESERAN RELASI BUDAYA TARI TOPENG AYU PADA MASYARAKAT TANON SEMARANG - Anik Purwati; Malarsih Malarsih; Agus Cahyono (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2019)
Dance, for instance, Topeng Ayu from Tanon Semarang is one of Javanese cultures which becomes living tradition. It is a cultural expression of Tanon people on the outskirts of Semarang. As a symbol and identity of society, this dance has become a cultural agenda to promote cultural attractions and education. Although there is a shift from traditional to modern, Tanon people has still stood on the existing ancestral traditions.    This phenomenon is interesting to be studied from its symbolic interaction, namely form of shift and its influence on culture, especially Topeng Ayu Dance. This research is descriptive qualitative and aims at revealing the meaning of research object action. It uses a sociological approach. Data were collected through observation, interviews, and documentation and analyzed with an interactive analysis model. The findings of this study indicated that Topeng Ayu Dance is a folk art as well as product of the local culture of the Tanon people which has unique characteristic and symbol of local society. The term of Topeng Ayu initially means tata lempeng hayuning urip, philosophy of life that encourages people to live in peace, harmony, and tolerance in the midst of existing plurality. The symbols of this dance moves convey meanings namely respect, both when maju beksan, beksan and mundur beksan as a form of social interaction to create an open society.